Os Processos de endoreduplicação e invasão de células trofoblásticas extravilosas humanas (linhagem HTR-8/SVneo) são influenciados pela presença do antígeno solúvel de Toxoplasma gondii - Martins, Camilla Manzan (2016)
Toxoplasma gondii is an obligate intracellular protozoan parasite able to infect many vertebrates, including the humans. In the vertical transmission of toxoplasmosis, the parasite overcomes the placental barrier and may cause serious consequences to the fetus, such central nervous system complications, ocular toxoplasmosis or even miscarriage. Placenta, essential for pregnancy, provides nutrients to the embryo and favors conditions for implantation. During this process, events such as invasion and migration of extravillous trophoblast cells are essential to induce placentation and pregnancy success. The control of these cells invasiveness is regulated by intrinsic mechanisms such as genetic material endoreduplication. Thus, inadequate migration and invasion of extravillous trophoblast cells are associated with pregnancy disorders. Thus, this study aimed to evaluate if antigen soluble Toxoplasma gondii (STAg) could influence in the migration, invasion and endoreduplication processes of HTR- 8/SVneo extravillous trophoblast cells. Initially, HTR-8/SVneo cells were cultured in RPMI 1640, supplemented with 10% fetal bovine serum and antibiotics. Migration and invasion assays were performed by Transwell and Matrigel, respectively. Endoreduplication and metalloproteinases were evaluated using the Western Blotting technique by p57 and MMP 2/9 protein expression, respectively. Extravillous trophoblast cells HTR-8/SVneo treated with STAg decreased p57 protein intracellular expression in trophoblast cells treated compared to untreated cells. It was also observed an increase in the invasiveness of these cells when compared to the control group, as well as increased expression of metalloproteinase 2. STAg influences in the p57 protein expression and the decrease in this protein levels reduced the endoreduplication processes and either the number of giant cells, favoring the invasiveness of extravillous trophoblast cells by MMP-2.